2018
DOI: 10.1136/bjophthalmol-2018-312140
|View full text |Cite
|
Sign up to set email alerts
|

Three-year outcomes of small incision lenticule extraction (SMILE) and femtosecond laser-assisted laser in situ keratomileusis (FS-LASIK) for myopia and myopic astigmatism

Abstract: Long-term follow-up analysis suggested that both SMILE and FS-LASIK were safe and equally effective for myopic and astigmatic correction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
56
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 23 publications
14
56
0
2
Order By: Relevance
“…Sekundo et al [1] first introduced this new procedure in 2011. e first clinical study [2] of femtosecond lenticule extraction in China was also reported in 2011. Numerous clinical studies [3][4][5][6][7][8][9] suggested that SMILE is a safe and effective procedure for myopia correction, and the follow-up periods in these studies mostly spanned from 3 months to 3 years, but rarely up until 4 years [10][11][12][13][14]. In 2019, we [15] have previously compared the 5-year outcomes of SMILE and femtosecond laser-assisted LASIK (FS-LASIK) in patients with myopia.…”
Section: Introductionmentioning
confidence: 99%
“…Sekundo et al [1] first introduced this new procedure in 2011. e first clinical study [2] of femtosecond lenticule extraction in China was also reported in 2011. Numerous clinical studies [3][4][5][6][7][8][9] suggested that SMILE is a safe and effective procedure for myopia correction, and the follow-up periods in these studies mostly spanned from 3 months to 3 years, but rarely up until 4 years [10][11][12][13][14]. In 2019, we [15] have previously compared the 5-year outcomes of SMILE and femtosecond laser-assisted LASIK (FS-LASIK) in patients with myopia.…”
Section: Introductionmentioning
confidence: 99%
“…Then except for 12 duplicate reports, 67 papers underwent title and abstract screening.33 studies were excluded as a result of following reasons: 11 studies did not have control group, and just made a separate description of SMILE or FS-LASIK; and 7 studies' control groups were not SMILE and FS-LASIK; meanwhile there were 15 Studies whose subjects were not high myopia. Finally, there remained 10 studies [2,3,11,[14][15][16][17][18][19][20] that met our inclusion criteria and they were included in this meta-analysis. Table 1 summarized the main characteristics and the quality assessment of these 10 included studies, which were published from 2014 to 2019.…”
Section: Sensitivity Analysis and Publication Biasmentioning
confidence: 99%
“…The logMAR values of postoperative UDVA. Of these 10 articles, 4 [11,[14][15][16] reported the the logMAR values of postoperative UDVA. And we excluded the study by Likun Xia et al [11] in the first subgroup because its high sensitivity.…”
Section: Primary Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…(6) SMILE ve f-LASIK'i hastaların kontralateral gözleri üzerinde refraktif sonuçlar açısından karşılaştırılmıştır. Refraktif sonuçlar açısından bazı yayınlarda SMILE ve f-LASIK'in sonuçlarının benzer olduğu bazılarında ise f-LASIK'in bir miktar daha etkili olduğu belirtilmiştir (3,4,6,7) . Ancak, bildiğimiz kadarıyla bu konuda yapılmış prospektif, kontrol gruplu, çok merkezli, tek/çift kör, kanıt düzeyi yüksek bir çalışma yoktur.…”
Section: Introductionunclassified